The Influence of Slang on Social Interaction Students of SMA Negeri 1 Rengel: A Sociolinguistic Study Review - Usman, Fadhila Nur; Dinna, Nova Rahma; Irawan, Mohammad Maulidina (International Journal of Linguasphere, 2026)
This research will discuss the influence of slang in the social interaction of SMA Negeri 1 Rengel students with the study of sociolinguistic studies. The first problem is the level of familiarity of students with slang terms used by the younger generation today. Second, there is the level of frequency of students interacting with friends who use slang. Third, there is an influence of slang on communication in the school environment. Fourth, there is a level of difficulty communicating with friends who use slang. Finally, there is the influence of slang in strengthening friendship relationships. This research uses a sociolinguistic approach with the theory of sociolinguistic variables. The source of data used comes from filling out questionnaires by students of SMA Negeri 1 Rengel conducted online. The method used is a mixed method which consists of quantitative and qualitative methods. The results of this study found that slang has influenced the education area in rural areas. In the study of the influence of slang in the social interaction of students at SMA Negeri 1 Rengel, it shows that most of the students feel familiar with the notion of slang because of the dominance of the use of slang used in their school environment which has an impact on the influence in communication between students. This also explains the relationship with the research results which show a large percentage in the data results which reveal that these students more often use slang in communicating with their peers which then has an impact on each student’s understanding of the reception of information conveyed in slang.